Dissecting distinct proteolytic activities of FMDV Lpro implicates cleavage and degradation of RLR signaling proteins, not its deISGylase/DUB activity, in type I interferon suppression - Visser, Linda J.; Aloise, Chiara; Swatek, Kirby N.; Medina, Gisselle N.; Olek, Karin M.; Rabouw, Huib H.; de Groot, Raoul J.; Langereis, Martijn A.; de los Santos, Teresa; Komander, David; Skern, Tim; van Kuppeveld, Frank J. M. (PLoS pathogens, 2020)
The type I interferon response is an important innate antiviral pathway. Recognition of viral RNA by RIG-I-like receptors (RLRs) activates a signaling cascade that leads to type I interferon (IFN-α/β) gene transcription. Multiple proteins in this signaling pathway (e.g. RIG-I, MDA5, MAVS, TBK1, IRF3) are regulated by (de)ubiquitination events. Most viruses have evolved mechanisms to counter this antiviral response. The leader protease (Lpro) of foot-and-mouth-disease virus (FMDV) has been recognized to reduce IFN-α/β gene transcription; however, the exact mechanism is unknown. The proteolytic activity of Lpro is vital for releasing itself from the viral polyprotein and for cleaving and degrading specific host cell proteins, such as eIF4G and NF-κB. In addition, Lpro has been demonstrated to have deubiquitination/deISGylation activity. Lpro's deubiquitination/deISGylation activity and the cleavage/degradation of signaling proteins have both been postulated to be important for reduced IFN-α/β gene transcription. Here, we demonstrate that TBK1, the kinase that phosphorylates and activates the transcription factor IRF3, is cleaved by Lpro in FMDV-infected cells as well as in cells infected with a recombinant EMCV expressing Lpro. In vitro cleavage experiments revealed that Lpro cleaves TBK1 at residues 692-694. We also observed cleavage of MAVS in HeLa cells infected with EMCV-Lpro, but only observed decreasing levels of MAVS in FMDV-infected porcine LFPK αVβ6 cells. We set out to dissect Lpro's ability to cleave RLR signaling proteins from its deubiquitination/deISGylation activity to determine their relative contributions to the reduction of IFN-α/β gene transcription. The introduction of specific mutations, of which several were based on the recently published structure of Lpro in complex with ISG15, allowed us to identify specific amino acid substitutions that separate the different proteolytic activities of Lpro. Characterization of the effects of these mutations revealed that Lpro's ability to cleave RLR signaling proteins but not its deubiquitination/deISGylation activity correlates with the reduced IFN-β gene transcription.